1996
DOI: 10.1001/archpsyc.1996.01830110060007
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence, Demographic Risk Factors, and Diagnostic Validity of Nonaffective Psychosis as Assessed in a US Community Sample

Abstract: Lifetime prevalence estimates of psychosis in community samples are strongly influenced by methods of assessment and diagnosis. Although results using computer algorithms were similar in the National Comorbidity Survey and Epidemiologic Catchment Area studies, diagnoses so obtained agreed poorly with clinical diagnoses. Accurate assessment of psychotic illness in epidemiologic samples may require collection of extensive contextual information for clinician review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
410
6
11

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(447 citation statements)
references
References 38 publications
20
410
6
11
Order By: Relevance
“…In the general population, non-clinically trained interviewers have carried out structured interviews to identify psychotic disorders (Robins & Regier, 1991 ;Kendler et al 1996) and psychotic symptoms . If anything, even greater difficulties have been encountered with the identification of psychotic rather than neurotic disorders.…”
Section: Structured Diagnostic Interview Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, non-clinically trained interviewers have carried out structured interviews to identify psychotic disorders (Robins & Regier, 1991 ;Kendler et al 1996) and psychotic symptoms . If anything, even greater difficulties have been encountered with the identification of psychotic rather than neurotic disorders.…”
Section: Structured Diagnostic Interview Assessmentsmentioning
confidence: 99%
“…If anything, even greater difficulties have been encountered with the identification of psychotic rather than neurotic disorders. Most recently, the diagnostic validity of a structured assessment of non-affective psychosis by non-clinically trained interviewers was assessed by clinician reinterviews and it was found that the diagnoses so obtained agreed very poorly with clinical diagnoses (Kendler et al 1996).…”
Section: Structured Diagnostic Interview Assessmentsmentioning
confidence: 99%
“…Similarly National Comorbidity Survey (NCS) (Kessler et al, 1994;Kendler et al, 1996) reveals 45% of comorbidity between substance abuse and schizophrenia while more recent National Comorbidity Survey Replication (NCS-R) (Kessler et al, 2005) reports 26.8% of lifetime comorbidity of non-affective psychosis with SUD. Furthermore, epidemiological investigations conducted outside United States support high prevalence of both substance abuse in psychotic disorders (Kavanagh et al, 2004;Addington and Addington, 2007) and SUD in schizophrenia (Fowler et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several important mental disorders, such as schizophrenia and personality disorders, were not assessed in the WMH surveys because the interview would have been difficult due to the stigma associated with these disorders. Previous validation studies have shown that disorders such as psychotic disorders are overestimated in lay-administered interviews such as the CIDI [20]. An additional limitation is that the study was a descriptive epidemiological study, and we were therefore unable to clarify the causal relationship between mental disorders and suicide ideation in community residents.…”
Section: Discussionmentioning
confidence: 91%